2017
DOI: 10.1108/ijmf-10-2016-0195
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance strength and stock market liquidity in Malaysia

Abstract: Purpose The purpose of this paper is to examine the impact of corporate governance strength on stock market liquidity in an emerging country, namely, Malaysia, by constructing a corporate governance score that captures both internal monitoring mechanisms (board of directors’ characteristics, audit committee’s characteristics and internal audit function) and external monitoring mechanism (audit quality). Design/methodology/approach The study uses a sample of 2,020 yearly firm observations in Bursa Malaysia ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 75 publications
3
33
0
1
Order By: Relevance
“…To control the potential reverse causality problem, Models 1 and 2 were re-estimated by using the lagged values of the independent variables (Al-Jaifi, 2017; Al-Jaifi, Al-Rassas, & AL-Qadasi, 2017;Al-Qadasi & Abidin, 2018;Alves, Couto, & Francisco, 2015;Miletkov, Poulsen, & Wintoki, 2014;Srinidhi, Gul, & Tsui, 2011). Table 6 shows that BCNDUAL, BCNMEM have a positive relationship with AEM and REM which is consistent with Table 5.…”
Section: Endogeneity Issue Of the Main Modelssupporting
confidence: 59%
“…To control the potential reverse causality problem, Models 1 and 2 were re-estimated by using the lagged values of the independent variables (Al-Jaifi, 2017; Al-Jaifi, Al-Rassas, & AL-Qadasi, 2017;Al-Qadasi & Abidin, 2018;Alves, Couto, & Francisco, 2015;Miletkov, Poulsen, & Wintoki, 2014;Srinidhi, Gul, & Tsui, 2011). Table 6 shows that BCNDUAL, BCNMEM have a positive relationship with AEM and REM which is consistent with Table 5.…”
Section: Endogeneity Issue Of the Main Modelssupporting
confidence: 59%
“…Furthermore, the work of the IA can also lead to a change in the costs of the external audit (Felix et al 2001). Abbott et al (2012) in particular substantiate this in the course of their study. They identify that the performance of IA increases the efficiency of the overall audit volume, which benefits both, the company and the external audit firms.…”
Section: Internal Auditing and Support Of The External Auditormentioning
confidence: 60%
“…But there is no consistent position in the literature on what this change looks like or whether it is exclusively positive or negative from an organizational perspective. On the one hand, it is argued that the effectiveness of IA leads to a reduction in the costs of the external audit, especially if IA covers areas of work relevant to the audit from an external perspective, such as accounting or fraud prevention and identification (Abbott et al 2012;Ho and Hutchinson 2010). On the other hand, there have been studies which have concluded that this relationship is not correct, as organizations may view the work of internal auditors and external auditors as complementary rather than substitutes (Singh and Newby 2010).…”
Section: Internal Auditing and Support Of The External Auditormentioning
confidence: 99%
“…The KSE was founded in 1947 and KSE 100 index was initiated in 1991 in which top 100 best performing companies were selected on the grounds of their capital. Like any other market, in KSE liquidity is considered as an important feature as it affects stock returns (Amer Al-Jaifi, Hussein Al-rassas, & Ali AL-Qadasi, 2017). Level of liquidity in any financial market is an important issue as high liquidity in stock market could result in the economic growth of the country.…”
mentioning
confidence: 99%